Media Interaktif Bermain dan Belajar Mengenal Buah-Buahan Berbasis Android Menggunakan Construct 2 - Pusvita, Ester Ayuk; Alexander, Kevin Yehezkiel (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
AbstractThe current era of globalization provides very rapid development in various fields, one of which is the development of games. By utilizing the element of play, it is proven to increase children's interest and involvement in the learning process. In addition, educational games can also help stimulate various aspects of child development, such as moral, physical, motor, cognitive, language, social-emotional, and artistic aspects. Getting to know various types of fruit is one of the important materials in early childhood education. Through fruit introduction, children can learn about the shape, color, taste, and benefits of different types of fruit. Fruit recognition can also help children develop observation, classification, and problem-solving skills. By using technology-based educational games, the fruit recognition process can be carried out more interestingly and interactively. Unfortunately, there are still many schools that rely on conventional learning methods in introducing fruit to students. This method often does not attract children's interest and attention, so the learning process becomes less effective. Based on the above background, the general purpose of this study is to develop a web-based educational game that can help early childhood in getting to know various types of fruits. By using this educational game, it is hoped that children can learn to recognize and distinguish different types of fruit through a fun and interactive way.Keywords: Constuct 2; Fruit; Game; Education; Android AbstrakEra globalisasi saat ini memberikan perkembangan yang begitu pesat di berbagai bidang, diantaranya  yaitu perkembangan di bidang permainan. Dengan memanfaatkan elemen permainan terbukti dapat meningkatkan minat dan keterlibatan anak dalam proses belajar. Selain itu, permainan edukasi juga dapat membantu menstimulasi berbagai aspek perkembangan anak, seperti aspek moral, fisik motorik, kognitif, bahasa, sosial emosional, dan seni. Mengenal aneka jenis buah merupakan salah satu materi penting dalam pendidikan anak usia dini. Melalui pengenalan buah, anak-anak dapat belajar tentang bentuk, warna, rasa, dan manfaat dari berbagai jenis buah. Pengenalan buah juga dapat membantu anak-anak mengembangkan keterampilan observasi, klasifikasi, dan pemecahan masalah. Dengan menggunakan permainan edukasi berbasis teknologi, proses pengenalan buah dapat dilakukan dengan lebih menarik dan interaktif. Sesuai dengan  latar belakang yang ada, fokus utama dari penelitian ini adalah untuk mengembangkan sebuah permainan edukasi berbasis web yang dapat membantu anak-anak usia dini dalam mengenal aneka jenis buah. Dengan menggunakan permainan edukasi ini, diharapkan anak-anak dapat belajar mengenali dan membedakan berbagai jenis buah melalui cara yang menyenangkan dan interaktif.